Sistem Informasi Penyewaan Alat Berat Berbasis Web Pada Cv. Trindo Jaya Pasifik Jambi - Afiz Sodik, Nafuri; Assegaff , Setiawan (Jurnal Manajemen Sistem Informasi, 2023)
CV.Trindo Jaya Pasifik Jambi is one of the companies located in the Jambi area where the heavy equipment rental system still uses books, agendas. So that there are problems, namely it is difficult to increase the number of orders in heavy equipment rental significantly, the slow dissemination of information for rental and how to rent heavy equipment in detail, and the availability and price of heavy equipment to be rented and the occurrence of obstacles in processing heavy equipment rental data in recording data. customer, The purpose of this research is to design a web-based heavy equipment rental system at CV.Trindo Jaya Pasifik Jambi. The method used in system design is the prototyping method. While the system modeling tools used by the author are Use Case Diagrams, Activity Diagrams, Class Diagrams. The prototype of this rental information system is expected to make it easier for CV.Trindo Jaya Pasifik Jambi to carry out the process of renting heavy equipment and facilitate the dissemination of the required information.